Lights and Shadows: Lived Experiences of Guidance Advocates in the Prac-tice of Ethical Bracketing - Decena, Aileen Joy B.; Singson, Deborah Natalia E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Due to the limited number of registered guidance counselors (RGCs) in the Philippines, public high schools are compelled to appoint classroom teachers as guidance advocates and perform the duties and responsibilities of an RGC, specifically facilitating counseling to learners. With their lack of training and fundamental knowledge, differing orientations, and demanding and overlapping work as classroom teachers and at the same time as guidance advocates, the participants are having difficulty practicing one of the ethical codes in the counseling profession – ethical bracketing; thus, its delivery is put to jeopardy. This study used descriptive phenomenological analysis to explore the lived experiences of guidance advocates on their practice of ethical bracketing in facilitating counseling services. Data were collected via unstructured in-depth interviews and analyzed using Lichtman’s three (3) C’s of Data Analysis, retaining only relevant themes: predicaments in ethical bracketing, factors for good ethical bracketing, transformation through counseling experiences, and counseling practice as a calling. The participants did not just overcome the challenges they had faced in practice but experienced transformations that significantly impacted their perspective about themselves, their counselees, and the counseling profession. The findings of this study serve as baseline information in creating a training program that can address the concerns of the guidance advocates on their practice of ethical bracketing in facilitating counseling services.